Being a grump only makes things worse: a transactional account of acute stress on mind wandering - Vinski, Melaina T.; Watter, Scott (Frontiers in Psychology, 2013)
The current work investigates the influence of acute stress on mind wandering. Participants completed the Positive and Negative Affect Scale as a measure of baseline negative mood, and were randomly assigned to either the high stress or low stress version of the Trier Social Stress Test. Participants then completed the Sustained Attention to Response Task (SART) as a measure of mind wandering behaviour. In Experiment 1, participants reporting a high degree of negative mood that were exposed to the high stress condition were more likely to engage in a variable response time, make more errors, and were more likely to report thinking about the stressor relative to participants that report a low level of negative mood. These effects diminished throughout task performance, suggesting that acute stress induces a temporary mind wandering state in participants with a negative mood. The temporary affect-dependent deficits observed in Experiment 1 were replicated in Experiment 2, with the high negative mood participants demonstrating limited resource availability (indicated by pupil diameter) immediately following stress induction. These experiments provide novel evidence to suggest that acute psychosocial stress briefly suppresses the availability of cognitive resources and promotes an internally-oriented focus of attention in participants with a negative mood.